Evaluation of law enforcement capabilities in safeguarding cultural property during armed conflicts - Farzullayeva Elkhan, Afet (Ius Humani. Jornal do direito, 2025)
The problem of protecting cultural heritage in hostilities is highly relevant, as demonstrated by the example of the Karabakh conflict. The primary purpose of the proposed work is to assess the effectiveness of law enforcement agencies' use of international and national legal norms and mechanisms for documentation, and to identify the main difficulties encountered along this path. The realization of the proposed goal involves using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) method, which makes it possible to analyze scientific sources and literature on the proposed issues. Likewise, the scientific methods of content analysis and comparison enable the processing of the collected sources and the highlighting of the most critical findings of other scholars. The results indicate that the conflict in Karabakh has undoubtedly threatened the local cultural environment. In the same way, the findings of this study contribute to the literature by providing a comprehensive assessment of the capacity of law enforcement agencies to protect cultural property. In that sense, the information obtained may serve as the basis for forming specific legal claims for compensation for the damage caused. This study addresses the existing gaps by defining the legal mechanisms for regulating the protection of cultural heritage and identifying the primary challenges in preserving it. Therefore, it was found that the limited resources available for conducting investigative actions lead to a lack of opportunities for organizing the restitution of cultural values. Finally, the conclusions note that an important aspect is that the history of Karabakh is overly politicised, which also does not contribute to the preservation of the region's cultural heritage.